Financial Strategy, Studies in the Creation, Transfer and Destruction of Shareholder Value (Book). - Burns, Thomas J.; Bremser, Wayne G. (The Accounting Review, 1980)
Reviews the book "Financial Strategy, Studies in the Creation, Transfer and Destruction of Shareholder Value," by William E. Fruhan.